2011
DOI: 10.1002/pssb.201100136
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced damage and destruction of HiPCO nanotubes in different gas environments

Abstract: 1074, Web: www.ltu.seWe have studied the thermal and chemical stability of HiPCOproduced single-walled carbon nanotube bundles to high laser power in air and argon. The samples were exposed to 110 kW/ cm 2 during 8 h with a 1.96 eV laser and the temperature was monitored via downshift of G þ -Raman peak. The structural changes in the carbon nanotubes (CNTs) caused by laser heating were monitored by recording their Raman spectra at ambient T (reference conditions) to ensure unaltered resonance conditions. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…52 In comparison, the shi of peaks was observed with laser powers at least 5 times higher. 53,54 The thermal inuence on the optical absorption spectra of SWCNT layers was also studied in situ. The absorbance measured for a different sample (see ESI, Fig.…”
Section: Temperature Dependencementioning
confidence: 99%
“…52 In comparison, the shi of peaks was observed with laser powers at least 5 times higher. 53,54 The thermal inuence on the optical absorption spectra of SWCNT layers was also studied in situ. The absorbance measured for a different sample (see ESI, Fig.…”
Section: Temperature Dependencementioning
confidence: 99%
“… , Even upon defunctionalization, which provides a second G outer contribution at high wavenumbers, the left shoulder peak corresponding to the G inner shifts to lower wavenumbers in correlation to higher laser power densities. Furthermore, it has been shown that a high power density laser, such as that used here, is capable of heating CNTs to 300–800 °C. , Additionally, the annealing exhibited a strong dependence on the Tube^2 film thickness. We found that for a thicker film, a lower power density was required to induce laser writing (Figure S6).…”
Section: Resultsmentioning
confidence: 78%
“…The presence of much smaller NiO No significant flaws are observed in the inner part of the CNTs. Previous works report the formation of different types of damage in CNT submitted to laser irradiation [47,48]. Furthermore, profuse laser-induced effects can lead to complex structural modifications such as unzipping of CNT to graphene nanoribbons, and even their transformation to polymers [49,50].…”
Section: Resultsmentioning
confidence: 99%